The Role of Public Service Apparatus Competence at SAM Ratulangi Hospital, Tondano - Zeke, Hesty H. Y.; Masengi, Evi; Kairupa, Sisca B. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to determine, analyze and describe the Competency Role of Public Service Apparatus at Sam Ratulangi Tondano Regional Hospital. The research method used is descriptive Qualitative. The number of informants in this study is 5 people. Data collection using Observation, interview and Documentation techniques. Data analysis through Data Reduction, Data Presentation and Conclusion Drawing. The results of the research show that it concludes that the Competency Role of Public Service Apparatus at RSUD Sam Ratulangi Tondano has been running well supported by the information that the researcher gets that: 1) The service procedure is sufficiently maximum given by officers at RSUD Sam Ratulangi Tondano 2) The Completion Time, is quite maximum because it is based on the SOP and also the Law but there are still obstacles related to when the service time begins, 3) the cost of service there are several types of services that do require individual costs, 4) facilities and infrastructure are sufficient, 5) the competence of service providers is good enough to be seen from the services provided